Scan matching based on hill climbing algorithm - Ang, Jimmy (2011)
The ability to simultaneously determine the location of robot while accurately map its unfamiliar surrounding is considered by many as essential key to make a robot truly autonomous. When a robot moves in an unknown environment, they have no absolute reference frame for its position, other than the features detected by its sensor. This problem of localization and mapping is known as Simultaneous Localization and Mapping (SLAM). In most SLAM problem, we usually find that odometry, LIDAR are used in giving initial estimation to solve this localization and mapping problem. In this paper, we tried to find a solution for SLAM problem by substituting odometry with IMU (Inertial Measurement Unit). IMU is a device consists of gyroscope and accelerometer where it is able to give the estimation for change of orientation.